Fulfillment of the Rights of Honorary Teachers in View of the Employment Law (Case Study at the Asy-Syarif Sidang Koto Laweh Islamic Boarding School) - Hakim, Ahmad Rais; Rusli, Benni; Irianto, Kartika Dewi (Universitas Ibn Khaldun Bogor, 2024)
The aim of the Preamble to the 1945 Constitution of the Republic of Indonesia is to make the nation's life more intelligent through education provided by the government and private foundations. In private foundations there are two honorary staff, namely government honorary teachers (PKWT) and foundation honorary teachers who are the focus of researchers, namely bald book teachers. Regarding the government's honorary rights, they are given based on the PKWT law, while the foundation's honorary rights are given by the Foundation in accordance with the labor law on labor, because bald book teachers who are appointed by the foundation are subject to labor law. The method in this research uses field research methods carried out at the Asy-Syarif Sidang Koto Laweh Islamic Boarding School. The results of research that took place in the field were that the rights of honorary foundation teachers (gubar bald teachers) had not been fulfilled in accordance with the labor law regarding workers in articles 86 concerning legal protection, 89 and 90 concerning labor wages. Because the wages given are far from the regional minimum wage, in order to meet the welfare of living, bald book teachers have to look for side jobs to make ends meet, the government should be quick to catch up to resolve this problem because the labor law regarding workers has not been implemented.